Harmonized definition of occupational burnout: A systematic review, semantic analysis, and Delphi consensus in 29 countries - Guseva Canu, Irina; Marca, Sandy Carla; Dell'Oro, Francesca; Balázs, Ádám; Bergamaschi, Enrico; Besse, Christine; Bianchi, Renzo; Jovanka Bislimovska; Koscec Bjelajac, Adrijana; Bugge, Merete; Busneag, Carmen Iliana; Çağlayan, Çiğdem; et al. (Scandinavian Journal of Work, Environment and Health, 2020)
Objective A consensual definition of occupational burnout is currently lacking. We aimed to harmonize the definition of occupational burnout as a health outcome in medical research and reach a consensus on this definition within the Network on the Coordination and Harmonisation of European Occupational Cohorts (OMEGA-NET). Methods First, we performed a systematic review in MEDLINE, PsycINFO and Embase (January 1990 to August 2018) and a semantic analysis of the available definitions. We used the definitions of burnout and burnout-related concepts from the Systematized Nomenclature of Medicine Clinical Terms (SNOMED-CT) to formulate a consistent harmonized definition of the concept. Second, we sought to obtain the Delphi consensus on the proposed definition. Results We identified 88 unique definitions of burnout and assigned each of them to 1 of the 11 original definitions. The semantic analysis yielded a first proposal, further reformulated according to SNOMED-CT and the panelists` comments as follows: "In a worker, occupational burnout or occupational physical AND emotional exhaustion state is an exhaustion due to prolonged exposure to work-related problems". A panel of 50 experts (researchers and healthcare professionals with an interest for occupational burnout) reached consensus on this proposal at the second round of the Delphi, with 82% of experts agreeing on it. Conclusion This study resulted in a harmonized definition of occupational burnout approved by experts from 29 countries within OMEGA-NET. Future research should address the reproducibility of the Delphi consensus in a larger panel of experts, representing more countries, and examine the practicability of the definition.
Keywords: Delphi consensus; epidemiology; exhaustion; job stress; occupational burnout; occupational health; semantic analysis; systematic review